CommLog© A communication log system for clinical trials. - Keyuan Jiang (IEEE Transactions on information technology in biomedicine)
Thanks to the advent of information technologies, the emergence of commercial products for electronic clinical trials has improved many aspects of conducting clinical trials. While there are many new options available to facilitate the collection of patient data, little advancements have been made in the way in which information generated from the coordination of a clinical trial is managed. The coordination of a clinical trial has proven to have a significant impact on the quality and economy of clinical trials. The Vanderbilt Coordinating Center has designed and implemented a communication log system (CommLog©) to streamline the coordination of clinical trials in order to improve the quality and economy of clinical trials. The CommLog© has been operational for several industry-sponsored phase II/III clinical trails and has provided a knowledge base for the studies and repository for useful study information.